2021
DOI: 10.3389/fpls.2021.767882
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Profiling Reveals Defense-Related Genes Against Ralstonia solanacearum Infection in Tobacco

Abstract: Bacterial wilt (BW) caused by Ralstonia solanacearum (R. solanacearum), is a vascular disease affecting diverse solanaceous crops and causing tremendous damage to crop production. However, our knowledge of the mechanism underlying its resistance or susceptibility is very limited. In this study, we characterized the physiological differences and compared the defense-related transcriptomes of two tobacco varieties, 4411-3 (highly resistant, HR) and K326 (moderately resistant, MR), after R. solanacearum infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…Seeds were grown in a glasshouse with natural light. A strain of R. solanacearum with a strongly aggressive defoliation was applied to the experiment of peanut inoculation [ 56 ]. TTC solid medium was used to revitalize the storage of glycerol (final concentration 25%) of R. solanacearum , stored in an ultra-cold storage freezer, and incubated at 28 °C for 48–72 h [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…Seeds were grown in a glasshouse with natural light. A strain of R. solanacearum with a strongly aggressive defoliation was applied to the experiment of peanut inoculation [ 56 ]. TTC solid medium was used to revitalize the storage of glycerol (final concentration 25%) of R. solanacearum , stored in an ultra-cold storage freezer, and incubated at 28 °C for 48–72 h [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…Plant-R. solanacearum associated transcriptomic data suggest the involvement of the cell wall in response to R. solanacearum infestation (Supplementary Table S1). For example, many upregulated genes in resistant tobacco 4,411-3 are involved in cell wall macromolecular metabolic processes and cell wall organization or biogenesis after inoculation with R. solanacearum (Pan et al, 2021). In peanut, cell wall-related genes showed specific expression differences between resistant and susceptible peanuts (Chen et al, 2014).…”
Section: Cell Wall Involvement In the Fight Against Ralstonia Solanac...mentioning
confidence: 99%
“…This suggestion was supported by Li et al (2021), who demonstrated that glutathione metabolism and phenylpropanoid pathways are the primary resistance pathways to Rs infection in tobacco. DEGs in glutathione metabolism were detected in the stems of a highly Rs-resistant tobacco variety as well (Pan et al, 2021). Glutathione is the most abundant antioxidant in cells and protects cell membranes and biomolecules from damage caused by reactive oxygen species (Dorion et al, 2021).…”
Section: Rs Infectionmentioning
confidence: 99%